2004
DOI: 10.2174/1568011043482142
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of the Binding Sites of P-Glycoprotein for Multidrug Resistance-Related Drugs and Modulators

Abstract: A major problem in cancer treatment is the development of resistance to multiple chemotherapeutic agents in tumor cells. A major mechanism of this multidrug resistance (MDR) is overexpression of the MDR1 product P-glycoprotein, known to bind to and transport a wide variety of agents. This review concentrates on the progress made toward understanding the role of this protein in MDR, identifying and characterizing the drug binding sites of P-glycoprotein, and modulating MDR by P-glycoprotein-specific inhibitors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 174 publications
(258 reference statements)
3
69
1
1
Order By: Relevance
“…The end products of the hydrolysis are intracellular ADP and inorganic phosphate (for recent reviews, see Refs. 13,34,48,102,118,123,156,210,213,300,313,322,331,389). Based on this molecular mechanism of action, the catalytic and transport properties of MDR-ABC transporters are significantly different from those of the P-type ATPases.…”
Section: Conserved Domains Structural Motifs and Catalytic Mechanismmentioning
confidence: 99%
“…The end products of the hydrolysis are intracellular ADP and inorganic phosphate (for recent reviews, see Refs. 13,34,48,102,118,123,156,210,213,300,313,322,331,389). Based on this molecular mechanism of action, the catalytic and transport properties of MDR-ABC transporters are significantly different from those of the P-type ATPases.…”
Section: Conserved Domains Structural Motifs and Catalytic Mechanismmentioning
confidence: 99%
“…[9] Summarizing data obtained by competition with photolabeling drugs Safa proposed seven binding sites that partly interacted with each other: a vinblastine binding site, which also bound verapamil and cyclosporine A; a taxol binding site; a binding site for dihydropyridine type calcium channel blockers; a binding site for bepridil, prenylamine, and megesterol acetate; for flupentixol; for prazosinlike structures; and Hoechst 33342. [10] Loo and Clarke reported many results from cross-linking experiments on the interaction and transport characterization of P-gp. [11][12][13][14] Differences in the cross-linking patterns observed upon binding of different drugs led them to suggest that P-gp could accommodate varying substrates through an induced-fit mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Two distinct substrate-binding sites, H (Hoechst 33342 binding site) and R (Rhodamine 123 binding site), have been pharmacologically defined for P-glycoprotein (19). Competition experiments subsequently suggested that P-glycoprotein could contain at least seven different drug-binding sites (20). The crystal structures of mouse and nematode P-glycoprotein, together with biochemical data, indicate that these proteins contain a large internal binding cavity that can accommodate structurally unrelated compounds of different sizes and shapes (21,22).…”
mentioning
confidence: 99%